A proposed ''A to Z RAM (Radiograph Assessment Method)'' for triage of patients with a suspected bone tumour. Issue 3 (August 2021) - Salunke, A.A.; Nandy, K.; Kamani, M.; Puj, K.; Pathak, S.; Patel, K.; Bhalerao, R.H.; Jain, A.; Sharma, M.; Warikoo, V.; Bhatt, S.; Rathod, P.; et al.
Abstract: Introduction: We propose a ''A to Z RAM (Radiograph Assessment Method)'' for evaluation of Radiograph of patients with a suspected bone tumour. Methods: In the current study, ten radiological features with letters 'A, B, C, D, E, F and Z' were used and which included the age of the patient, involved part of the bone, characteristics, content, distinctiveness, the exterior of the bone, fracture, and zone of transition. Four independent observers (orthopaedic oncologists and surgical oncologists) evaluated a set of 30 radiographs of bone tumour selected at random from our hospital database based on A to Z RAM. We classified the lesions into two groups according to the traffic signal system; Green (suspected benign lesion) and Red (suspected malignant lesion). Results: There were 18 (60%) benign bone lesions and 12 (40%) malignant lesions in the current study. 91.6% of malignant tumours and 88.8% of the benign tumours were identified correctly by the four observers. The inter-observer variability with Fleiss kappa was 0.884 (95% CI 0.7–1.03 p-value < 0.05), suggestive of agreement not by chance. These radiographs were again reassessed by the four observers after 3 months. The interobserver variability by Fleiss kappa was 1.0 (95% CI 0.8–1.1) suggesting complete agreement amongst the observers. Both orthopaedic oncologists had intra-observer kappa as 1.0 each and both surgical oncologists had 0.795 and 0.930 respectively. Conclusion: The proposed A to Z RAM is an easy to use and reproducible method for reviewing radiographs in the out-patient department along with clinical findings for better management of patients with suspected bone lesions. The A to Z RAM can be a medical triage tool and subdivide bone lesions into two subgroups i.e. suspected benign lesion with a suggestion of further investigations with MRI and biopsy and suspected malignant lesion with a suggestion of MRI or early referral to a tertiary cancer center with expertise in orthopaedic oncology. Implications for practice: The A to Z RAM (Radiologic Assessment Method) is a reproducible method for reviewing radiographs in the out-patient department and can be an aid for better management of patients. A to Z RAM is useful as a medical triage system, subdividing patients according to the probable diagnosis into a suspected benign lesion and suspected malignant lesion.